Compromising and Repositioning the Meaning of Corruptors as Thieves in Applying the Provisions of Shara’ into the Modern Era Context - Helmina, Helmina; Harun, Hermanto; Witro, Doli; Ardi, Muh Zaitun; Busni, Darti (al-'adalah, 2024)
The debates on the application of Islamic criminal law in various Muslim-majority countries are still ongoing. This is because these countries still adhere to a positive legal system. This phenomenon has spread to many things including implementing the punishment of cutting off the hands of corruptors as is the punishment for thieves in the provisions of Islamic criminal law. One of the obstacles, in this case, is due to differences of opinion on the use of the term "thief" to be applied to "corruptor". This article aims to analyze the punishment provisions for thieves as regulated in Surah al-Maidah verse 38 to be applied to perpetrators of corruption. This article is the result of qualitative research with a linguistic approach. The primary data source in this study is the Qur'an, whereas, the secondary data sources are articles, books, and other relevant documents. Data were collected through a literature study method which was then processed, analyzed, and concluded. This study found that the crime of corruption, seen from a linguistic perspective, has the same meaning as thievery; the perpetrator, therefore, can be sentenced to the same punishment (cutting off the hand). The punishment here is the most severe type that can be imposed on perpetrators of corruption, considering that the impact it causes is heavier and wider than the impact that arises in the crime of thievery. Certainly, this punishment is applied if it has met all the elements and legal requirements and is applied in a very strict manner.